Somatosensory alpha oscillations gate perceptual learning efficiency - Marion Brickwedde (Nature Portfolio, 2019)
Alpha power is known to play an important role in cognition and perception, but we do not understand the link between alpha power and perceptual learning efficacy. Here, the authors use neurofeedback training to show that increased alpha power enhances learning while reduced alpha impedes learning.